The complete blood count height - Chiodi, Hugo (1951)
The study of the complete blood count in normal subjects was performed at 4515 m permanent residents. on sea level. It was observed: 1) Increased hemoglobin, red blood cell count and erythrocyte volume, with wide individual variations, there is no relationship between the hematopoietic response and duration of hypoxia. Polycythemia is normocytic type. 2) Alteration of the leukocyte formula consistent increased with decrease Mononuclear Cell polynuclear neutrophils but without noticeable changes in the total number of leukocytes. 3) Delay the sedimentation rate of erythrocytes.